Use of media in preschool education: a case study from Ukraine - Ponomarenko, Tetiana O.; Proshkin, Volodymyr V.; Shynkar, Tetiana Yuriivna; Holovatenko, Tetiana Yuriivna; Головатенко, Тетяна Юріївна (Hershey-New York-London-Beijing : IGI Global Scientific Publishing, 2025)
The article explores the unique challenges of utilizing media in preschool education amid the war in Ukraine. It analyzes scholarly research on the use of traditional and innovative media in teaching preschool children. The research employs a pre-test and post-test study design. The paper aims to study the features and level of development of cognitive activity in six-year-old children and the ability of educators to utilize media. It presents the experience of using media in various forms of interaction between educators and children and professional training of educators on the possibilities of using media. The main findings indicate positive outcomes of the experimental intervention on the cognitive development of six-year-old children. The use of various media tools by educators significantly contributed to improvements in all three criteria of cognitive activity: emotional-motivational, cognitive-activity, and personality-volitional. It demonstrates the effectiveness of using media to enhance the cognitive development of six-year-old children.

У статті досліджуються унікальні виклики використання медіа в дошкільному вихованні в умовах війни в Україні. Аналізуються наукові дослідження щодо використання традиційних та інноваційних медіа у навчанні дошкільнят. Дослідження проводиться за методом пре-тесту та пост-тесту. Мета статті – дослідити особливості та рівень розвитку когнітивної діяльності шестирічних дітей та здатність педагогів використовувати медіа. У статті представлено досвід використання медіа в різних формах взаємодії між педагогами та дітьми, а також професійну підготовку педагогів щодо можливостей використання медіа. Основні висновки свідчать про позитивні результати експериментального втручання на когнітивний розвиток шестирічних дітей. Використання різних засобів масової інформації педагогами значно сприяло поліпшенню всіх трьох критеріїв когнітивної діяльності: емоційно-мотиваційного, когнітивно-активного та особистісно-вольового. Це демонструє ефективність використання засобів масової інформації для підвищення когнітивного розвитку шестирічних дітей.
Використання медіа в дошкільній освіті: кейс-стаді з України
Keywords: SOCIAL SCIENCES::Social sciences::Education; медіа; media; дошкільна освіта; preschool education